SELECTION OF AN OFFSHORE PETROLEUM PRODUCTION SYSTEM BY EVALUATING AN ENVIRONMENTAL IMPACT INDEX - Goncalves, Maiara Moreira; Morooka, Celso Kazuyuki; Guilherme, Ivan Rizzo [UNESP]; ASME (Amer Soc Mechanical Engineers, 2014)
The development of an offshore petroleum production system corresponds to define a set of equipment to make possible oil and gas extraction from an underwater petroleum reservoir. To better comprehension of the process, definition of this production system can be divided into phases. Phase I corresponds to the selection of number of wells and type of the well. Then, following the previous work (Franco, 2003), in the Phase II, the layout arrangement of wells and the set of the stationary Floating Production Unit (FPU) are selected. And, in the Phase III, storage and offloading alternatives for the produced oil and gas are selected. The present paper aims to identify environmental impacts associated with the each component of an offshore system for oil and gas production, and quantify each of them through indexes. It is expected to support the decision makers to select the best fitted system for a given offshore petroleum field. The increasing needs of petroleum to fulfill the energy matrix demanded in Brazil, the growing concern of the society for keeping the environment clean and the inclusion of an index related to the environment besides the technical and technological indexes usually taken makes it an important contribution to improve the process for selection and decision about the offshore production system. Particularly, it will be fundamental in the adverse condition of the Pre-salt scenario of petroleum production, in ultra-deep water depth and oil and gas with more aggressive contaminants to the system. The proposed methodology follows a similar procedure for the assessment of environmental impacts through the use of environmental sensitivity index (ESI) and the use of impact matrix (NOOA, 1997; Patin, 1999; Mariano and La Rovere, 2006). For the estimation of environmental impacts, it was defined the ESI of the area to be developed, and it was constructed an impact matrix based on the activities involved in the installation of platform, operational phase and decommissioning of a FPU and the elements from environment. Therefore, this systematic and structured approach allowed incorporating to the process of selection of the offshore production system for an oil and gas field the selection of alternative which combines the best technical and technological characteristics with better aspects from the environment.